Hubungan Asupan (Protein, Lemak, Zat Besi, Kalsium) dan Tingkat Stress dengan Siklus Menstruasi Remaja Putri - Utami, Yuliani Tri; Vidyarini, Andra (Pontianak Nutrition Journal (PNJ), 2024)
Menstruation is the discharge of blood from the uterus that occurs at a certain time. The menstrual cycle is very important in the female reproductive system because it influences circuit changes, however, many women experience menstrual cycle disorders which can have an impact on health. The research aims to analyze the relationship between intake (protein, fat, iron, calcium) and stress levels with the menstrual cycle of adolescent girls at SMA PGRI 1 Bekasi City. The method used is quantitative research with a cross-sectional design. This research involved 101 respondents using Purposive Sampling technique. Protein, fat, iron and calcium intake was obtained using the 2 x 24 hour recall method. The questionnaires and interviews used were the menstrual cycle and the DASS (Depression Anxiety Stress Scale) stress level. Analysis was carried out using the Chi-Square statistical test. Based on the research results, it can be seen that the majority of respondents have normal menstrual cycles, normal macro intake (protein, fat), low micro intake (iron, calcium) and moderate stress levels. The results of bivariate analysis showed that there was no relationship between intake (protein, fat, iron, calcium) and stress levels with the menstrual cycle (p>0.05). Conclusion There is no relationship between intake (protein, fat, iron, calcium) and stress levels with the menstrual cycle of adolescent girls at SMA PGRI 1 Bekasi City.